DEVELOPING MATH MODULE OF LINE MATERIAL AND CORNER IN SETTING COOPERATIVE LEARNING TYPE THINK PAIR SHARE (TPS) FOR CLASS VII SMP - Abdul Majid (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2013)
The study aims at producing package of learning module of cooperative learnig setting of think pair share type which fulfills the criteria of valid, practical, and effective. The study is research and development. The package of product to be produced consists of three components, namely lesson plan (RPP), Mathematics module learning (MPM), and test of learning result (THB). The development of the package employs 4-D Thiagarajan which conducted in four steps, namely defining phase, design phase, development phase, and dissemination phase. The result of study reveal that the package of the module is valid, practical, and effective based on the evaluation of the experts and the result of limited tryout. The validity of package of Matematics module based o the validation of experts has met valid criteria that (1) the co-efficient validity of RPP is 100%, (2) the co-efficient validity of Mathematics module is 85%, and (3) the co-efficient validity of THB is 83,3%. These indicate  that the package of Mathematics module is in valid category. The practicality of the package based on the observation of the implementation of the package has met the category of completely implemented. The effectiveness of the package has met four indicators of effectiveness which shown on (1) the percentage of classical graduates of learning result by 90,1%, (2) the fulfillment of 8 categories of students’ activity, (3) positive response by 80% students on learning process and Mathematics module, (4) teacher’ ability in managing the learning which in good category